Проблема пам’яті в романі Джонатана Сафрана Фоера «Усе освітлено» - Бежан, О. (Літературознавчі обрії. Праці молодих учених, 2010)
The article deals with the problem of individual and collective memory as the reflection of historical experience of the past. The research is based on Jonathan Safran Foer’s novel «Everything is Illuminated» (2002). Memory is regarded as a cultural and social construction that forms man’s identity. The author of the article also puts a question of national memory which is the part of collective past too.